Long-service-life rubber not prone to cracking - JIANG MUYUN (2020)
The utility model discloses rubber with long service life and low possibility of cracking. The rubber gasket comprises a rubber matrix, a sandwich layer, a ventilation structure, a combination plate and a braid layer, wherein a sandwich layer is fixed in the rubber base body; ventilation structures are uniformly mounted in the sandwich layer; a combining plate is mounted in the rubber base body onone side of the sandwich layer; a braid layer is fixed in the rubber base body; a buffer plate is mounted in the braided layer; top plates are evenly fixed in the combination plate above the ventilation structure, a concave frame is arranged on one side of each top plate, a gasket is installed at one end of each concave frame, a ventilation hole is formed in one end of the buffer plate, one end of each ventilation hole is fixedly connected with one end of the bearing plate, and an environment-friendly film is installed in the portion, on one side of the buffer plate, of the woven layer. According to the utility model